1993
DOI: 10.1577/1548-8675(1993)013<0856:cooasa>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Otolith and Scale Age Characteristics for Black Crappies Collected from South Dakota Waters

Abstract: Scales and otoliths (sagittae) were collected from black crappies Pomoxis nigromaculatus sampled during the spring of 1991 in Red Plum Reservoir and Roy Lake, South Dakota. Red Plum Reservoir contained a slow‐growing black crappie population, whereas Roy Lake had a fast‐growing population. Annuli in scales and otoliths were identified independently by three readers. Within‐structure (i.e., among‐reader) and between‐structure agreements in both population samples were 94% or greater for both scales and otoliths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 6 publications
0
31
0
Order By: Relevance
“…(Schramm andDoerzbacher 1985, Boxrucker 1986, Hammers andMiranda 199 1). In northern latitudes, precision of ages determined froin scales and otoliths for black crappie were similar (Kruse et al 1993). Additionally, most of the growth calculations from otoliths calculated length at age rather than by backcalculations.…”
Section: Discussionmentioning
confidence: 90%
“…(Schramm andDoerzbacher 1985, Boxrucker 1986, Hammers andMiranda 199 1). In northern latitudes, precision of ages determined froin scales and otoliths for black crappie were similar (Kruse et al 1993). Additionally, most of the growth calculations from otoliths calculated length at age rather than by backcalculations.…”
Section: Discussionmentioning
confidence: 90%
“…Scales have been shown to provide accurate and precise age estimates for some species, including largemouth bass (Micropterus salmoides; Prentice andWhiteside 1974, Long andFisher 2001), black crappie (Pomoxis nigromaculatus; Kruse et al 1993), and striped bass (Morone saxatilis; Welch et al 1993). Although scales perform well for many species, several studies have reported that scales tend to underestimate fish age (e.g., Marwitz and Hubert 1995, Kocovsky and Carline 2000, lsermann et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Age assignment from spines and scales was less precise than from otoliths for fish collected from upper Hudson river and for the older fish scale ages were progressively lower than otolith age (Maceina and Sammons, 2006). Kruse et al (1993) observed that ages determined using scales and otoliths were reported to be similar in black crappies, Pomoxis nigromaculatus (Lesueur). Erman (1959) found that annual rings on otoliths were more difficult to identify.…”
Section: Otolithsmentioning
confidence: 99%